Student Learning Evaluation Based on Artificial Intelligence. - Bhalerao, Chetak (Journal of Advanced Research in Applied Artificial Intelligence and Neural Network; Vol 3 No 1 (2019): Journal of Advanced Research in Applied Artificial Intelligence and Neural Network, 2021)
In this paper we are suggesting an artificial intelligence-based pupil knowledge assessment tool (AISLE) grounded on the idea maps to measure the level of considerate of a pupil. The key drive of this article is to progress the use of AI in valuation of pupil’s considerate using issue exact concept map. The paper will also systematize the pupil learning evaluation methods. It allows educator to measure pupil in additional deep and well-organized way. Primary of all, the theme exact concept map is created by the teacher and pupil. The knowledge is to allocate random scores to ideas in concept map created by pupil and calculate z score using z score algorithm. Founded on these scores the probability distribution of the ideas identified in the concept map will be intended.it is plotted in the form of graph. The evaluation of the overall learning will be done by analyzing the curve of graphs of pupils’ concept map and teacher’s (ideal) concept map. Teacher will be able to guess the exact thoughtful of multiple pupils concurrently. How to cite this article: Bhalerao C, Deshpande G, Neware G et al. Student Learning Evaluation Based on Artificial Intelligence. J Adv Res Appl Arti Intel Neural Netw 2019; 3(1): 34-34.